Interogational Sentences in the Novel “33 Senja di Halmahera” by Andaru Intan - Dwi Wulandari; Sudaryanto (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
This study examines interrogative sentences in the novel 33 Senja di Halmahera. The aims of this research are (1) to describe the types of interrogative sentences and (2) to describe the function of interrogative sentences in 33 Senja di Halmahera novel. Data collection methods and techniques in this study used the listening method with tapping techniques, follow-up techniques Listen, Free, Involved, Cakap (SBLC) and advanced note-taking techniques. The methods and techniques of data analysis in this study used the agih method with the basic technique for Direct Elements (BUL) and with advanced techniques of transformation techniques. The results of this study are (1) There are 5 types of interrogative sentences, namely: (a) Interrogative sentences that ask for a yes or no answer, are formed in three ways, namely giving question into the sentence symbolized by a question mark (?) as many as 64 data, giving a question word whether in front of a sentence as much as 1 data, and giving a question particle in the part of the sentence being asked as much as 23 data. b. Interrogative sentences that ask for answers regarding one element of the sentence are formed with the help of question words (what, who, where, how many, and when) as many as 32 data. c. Interrogative sentences that ask for answers in the form of reasons are 13 data. d. Interrogative sentences that ask for answers in the form of opinions are 24 data. e. Interrogative sentences that contain 8 data, (2) Functions of interrogative sentences are found as many as 8 functions. These functions consist of: a. What question words are 17 data, b. The question word who has 4 data, c. Question words why as many as 7 data, d. Question words why as many as 6 data, e. question words how as many as 23 data, f. which question words are 5 data, g. question words when, when, and when. as much as 5 data, h. the question word how much is 3 data.